Pemanfaatan Sistem Informasi Peta Layanan Kesehatan di Jawa Tengah Tahun 2019-2021 - Baharudin alamsyah; Bambang agus herlambang; Ahmad khoirul anam (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Health Service Map Information System (SIPLK) is a web application that provides spatial and non-spatial information about health services in Indonesia. The purpose of this study is to find out the utilization of SIPLK in improving access and quality of health services in Indonesia, especially in Central Java province. The method used is descriptive quantitative using secondary data from the Central Java Statistics Agency. The data analyzed are the data on the distribution of public health workers (TKM) in Central Java province in 2019-2021. The results of the study show that SIPLK can be used as a tool in planning, monitoring, and evaluating health services in Indonesia. The utilization of SIPLK can help health stakeholders in planning, allocating, and distributing TKM according to the needs and conditions of the community. This study recommends that SIPLK can be further developed by adding features that can enhance its function and benefit for users, such as search, filter, recommendation, and interaction features.